2023
DOI: 10.1039/d3sc00568b
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent photo-activated aminoborane room-temperature phosphorescence materials with unprecedented properties: simple, versatile, multicolor-tuneable, water resistance, optical information writing/erasing, and multilevel data encryption

Abstract: Triarylboranes-based pure organic room-temperature phosphorescent (RTP) materials are rarely investigated because of their large steric hindrance and electron defect of the boron atom. As a result, it is quite difficult...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Poly­(methyl methacrylate) (PMMA) is also a commonly used liposoluble polymer to construct amorphous pure organic RTP materials . Cao and co-workers synthesized two triarylborane derivatives, B- o -Met-Cz and BN- o -Met-CZ (Figure b), and doped them into a PMMA matrix at a concentration of 0.5 wt %. The BN- o -Met-CZ@PMMA with dimethylamino group presented excellent RTP performance (Φ RTP = 6.83%, τ RTP = 0.18 s), while B- o -Met-CZ@PMMA did not show any RTP.…”
Section: Construction Of Polymer-based Rtp Systemsmentioning
confidence: 99%
“…Poly­(methyl methacrylate) (PMMA) is also a commonly used liposoluble polymer to construct amorphous pure organic RTP materials . Cao and co-workers synthesized two triarylborane derivatives, B- o -Met-Cz and BN- o -Met-CZ (Figure b), and doped them into a PMMA matrix at a concentration of 0.5 wt %. The BN- o -Met-CZ@PMMA with dimethylamino group presented excellent RTP performance (Φ RTP = 6.83%, τ RTP = 0.18 s), while B- o -Met-CZ@PMMA did not show any RTP.…”
Section: Construction Of Polymer-based Rtp Systemsmentioning
confidence: 99%
“…4, bottom). Although spatiotemporal patterning using photoactivated phosphorescence materials has been reported recently, 29–31,41 this work provides the first example where not only emission but also absorption are spatiotemporally controlled based on photochemical reactions, as far as we know. Such spatiotemporal patterning is promising for applications including encryption technologies and display devices.…”
mentioning
confidence: 92%
“…Actually, photoactivated phosphorescence based on triplet quenching by molecular oxygen in gel or polymer-film matrices has recently attracted increasing attention in applications to encryption technology. 29–31 On the other hand, although clock or sigmoidal dynamics are seen in many photochemical reactions as well, 32,33 such clock behaviors have scarcely been utilized positively in photofunctional materials. This would be due to the difficulty in the oxygen control in solutions and the lack of reversibility.…”
mentioning
confidence: 99%
“…The rate of phosphorescence ( k p ) can be enhanced using a rare-earth metal-based organometallic complex, which increases the spin–orbit coupling (SOC), making the transition quantum-mechanically allowed. Since these systems are expensive, an alternative approach is needed to circumvent these limitations. Over the past decade, substantial progress has been made in developing organic blue-green and yellow-red RTP emitters with millisecond (ms) lifetimes for data security and sensors , due to their advantages of structural versatility and facile processability. It has been established that the RTP characteristics of most of the reported twisted geometries heavily rely on the heavy-atom effect, , El-Sayed’s rule, , the energy gap principle, ,,, El-Sayed analogy, donor–acceptor, donor–spacer–acceptor, and donor–sp 3 linker–acceptor. ,, In addition, the incorporation of intermolecular interactions, ,, aggregation, ,,, and rigid single crystals, along with host–guest studies , has also been demonstrated to significantly suppress radiationless decays ( k nr ).…”
Section: Introductionmentioning
confidence: 99%